Osteomyelitis: Pathophysiology, Clinical Manifestations, Diagnostic Evaluation, Microbiological Characteristics, Contemporary Therapeutic Strategies, and Recent Advances in the Prevention and Management of Bone Infection-An Updated Review - Alharthi, Abdual rahman Faihan H.; Alharbi, Muqbil Abdullah Muqbil; Onayzan, Mohammed Ayidh; Alshammari, Abdulrahman Assaf Darwish; Alanazi, Meshal Suwaydir Saad; Almazariqah N., Saad Saeed; Nawar Alotaibi, Abdullah Mathkar; Saeed, Turky Faez; Alharbi, Sari Rashed Saleh; Alrashid, Mohammed Ayidh Onayzan (International Journal of Aquatic Research and Environmental Studies, 2025)
Background: Osteomyelitis is a complex and potentially disabling infectious disease of bone and bone marrow that remains a significant clinical challenge despite advances in diagnostic and therapeutic strategies. Progressive bone inflammation, microbial persistence, and extensive tissue destruction contribute to considerable morbidity, impaired function, and reduced quality of life when diagnosis or treatment is delayed. The predominance of Staphylococcus aureus and its sophisticated virulence mechanisms, including biofilm formation, intracellular persistence, phenotype switching, and invasion of the osteocyte lacuno-canalicular network, further complicate disease management and increase the risk of chronic infection. Aim: This review aimed to comprehensively summarize the current evidence regarding the pathophysiology, microbiology, clinical manifestations, diagnostic approaches, therapeutic strategies, and emerging advances in the prevention and management of osteomyelitis. Methods: A comprehensive narrative review of the contemporary literature was conducted to evaluate current evidence on the mechanisms of disease, causative microorganisms, clinical presentation, diagnostic modalities, antimicrobial therapy, surgical management, biomaterial-based interventions, and novel therapeutic approaches for osteomyelitis. Results: Current evidence demonstrates that Staphylococcus aureus remains the principal pathogen responsible for osteomyelitis through multiple virulence mechanisms that promote chronicity and antimicrobial resistance. Magnetic resonance imaging is the most sensitive imaging modality for early diagnosis, whereas bone biopsy with microbiological culture and histopathological examination remains the diagnostic gold standard. Management requires a multidisciplinary approach integrating accurate microbiological diagnosis, targeted antimicrobial therapy, and appropriate surgical debridement when indicated. Recent evidence supports shorter intravenous antibiotic courses followed by oral therapy in selected uncomplicated cases, whereas chronic osteomyelitis requires prolonged pathogen directed antimicrobial treatment combined with extensive surgical intervention. Conclusion: Successful management of osteomyelitis requires early diagnosis, individualized multidisciplinary treatment, and integration of medical and surgical interventions. Emerging biomaterial technologies and targeted antimicrobial strategies offer considerable potential to improve treatment outcomes, reduce recurrence, and enhance bone healing. Continued research is essential to optimize treatment duration, develop therapies targeting persistent intracellular pathogens, and establish evidence-based protocols for incorporating regenerative biomaterials into routine clinical practice.